A critical review of energy resources, policies and scientific studies towards a cleaner and more sustainable economy in Vietnam - Nong D. (Elsevier Ltd, 2023)
Climate change; Commerce; Decision making; Energy policy; Investments; Personnel; Pollution control; Renewable energy resources; Cleaner production; Development plans; Institutional barriers; Power development; Power development plan; Renewable energies; Renewable Power; Scientific studies; Sustainable economy; Viet Nam; Energy efficiency